Long-term survival of sorafenib-treated FLT3-ITD–positive acute myeloid leukaemia patients relapsing after allogeneic stem cell transplantation. (November 2017) - Metzelder, S.K.; Schroeder, T.; Lübbert, M.; Ditschkowski, M.; Götze, K.; Scholl, S.; Meyer, R.G.; Dreger, P.; Basara, N.; Fey, M.F.; Salih, H.R.; Finck, A.; et al.
Abstract: Background: Fms-like tyrosine kinase 3 internal tandem duplication (FLT3-ITD)–positive acute myeloid leukaemia (AML) relapsing after allogeneic stem cell transplantation (allo-SCT) has a dismal prognosis with limited therapeutic options. FLT3-ITD kinase inhibition is a reasonable but palliative experimental treatment alternative in this situation. Information on long-term outcome is not available. Methods: We performed a long-term follow-up analysis of a previously reported cohort of 29 FLT3-ITD–positive AML patients, which were treated in relapse after allo-SCT with sorafenib monotherapy. Findings: With a median follow-up of 7.5 years, 6 of 29 patients (21%) are still alive. Excluding one patient who received a second allo-SCT, five patients (17%) achieved sustained complete remissions with sorafenib. Four of these patients are in treatment-free remission for a median of 4.4 years. Interpretation: Sorafenib may enable cure of a proportion of very poor risk FLT3-ITD–positive AML relapsing after allo-SCT. Highlights: Sorafenib induces long-term survival in Fms-like tyrosine kinase 3 internal tandem duplication (FLT3-ITD)+ acute myeloid leukaemia (AML) relapsing after allogeneic stem cell transplantation (allo-SCT). Sorafenib cures a minority of FLT3-ITD+ AML relapsing after allo-SCT. Achievement of molecular negativity is strongly associated with cure.